Navigating Surgical Strategies for Symptomatic Tarlov Cysts: A Case Report of Successful Microsurgical Excision and Imbrication - Arip Heru Tripana; Tondi Maspian Tjili; Afdal; Ismar; Eko Setiawan (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Symptomatic Tarlov (perineural) cysts are a rare but debilitating cause of chronic radicular pain, arising from cerebrospinal fluid (CSF) accumulation within the nerve root sheath. The diagnostic journey is often complex, requiring a definitive link between the lesion and the patient's symptoms, and the optimal surgical strategy remains a subject of considerable debate. Case presentation: A 56-year-old male presented with a six-month history of intractable right S2 radiculopathy (VAS 8/10) and severe functional impairment (Oswestry Disability Index 78%), which had failed a comprehensive trial of conservative management. Magnetic resonance imaging revealed a large cystic lesion at the right S2 level, with features characteristic of a Tarlov cyst, causing severe nerve root compression. Following a thorough discussion of the risks and benefits, the patient underwent an S2 laminectomy with microsurgical partial cyst excision and wall imbrication. Postoperative histopathology confirmed the diagnosis of a perineural cyst, identifying nerve fibers within the fibroconnective tissue of the cyst wall. Conclusion: The patient experienced immediate and sustained resolution of his radicular pain (VAS 0/10) and a profound improvement in functional status (ODI 12%) at one-year follow-up, with radiological confirmation of successful cyst obliteration. This case highlights the potential of a direct microsurgical approach, guided by a strong clinical-radiological correlation and confirmed by histopathology, to provide a durable and life-altering cure for patients disabled by symptomatic Tarlov cysts.